Penerapan Ekstrakurikuler Kerohanian Islam (KEROHANIAN ISLAM) Untuk Meningkatkan Kecerdasan Spiritual Siswa Kelas XI di SMK Insan Bina Generasi 3 Bogor Jawa Barat Tahun Ajaran 2023-2024 - Sudarma, Sudarma; Saidah Yusrie, Chaira H; Riyanto, Riyanto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
The low spiritual intelligence of students causes excessive fanaticism, weak faith, loss of soul control and is prone to deviate from religious understanding and values in general. With the implementation of religious programs outside of learning to strengthen the spirituality of the students who participate in these activities. This research will examine the technicalities of implementing extracurricular Islamic spiritual guidance, what are the aspects that hinder and support Islamic spiritual guidance activities, and whether Islamic spiritual guidance activities will increase the religious awareness of students in Batch 2024. This was done to examine its impact on improvement. This study used descriptive qualitative research conducted over several months from April 6, 2023 to January 14, 2024 at SMK INSAN BINA GENERASI 3 Bogor, West Java. The subjects of this research were the Islamic Spirituality trainers of SMK INSAN BINA GENERASI 3 Bogor, West Java. The research informants are the person in charge and the Islamic Spirituality Advisor as well as the Islamic Spirituality Members. The techniques used in this research are observing Islamic spiritual activities directly, processing participant data, and interviewing. Verification of the truth of the research material is based on data triangulation. The method of elaboration uses the method of analyzing various data sources.The stages then carried out are detailed discussion of data, presentation of materials, and drawing out the final results.The results of this research have a very big influence on the world of education. Extracurricular Islamic Spirituality (Kerohanian Islam) is carried out regularly every Saturday.The mentoring process usually takes place through the provision of educational materials using learning media and applications.We use three approaches when conducting extracurricular teaching activities in Kerohanian Islam: exploring the potential of members, a personal approach, and an ideal role model approach. Assessment in Islamic Spirituality activities includes exams recorded on the questions given, communication techniques, and internships. The inhibiting aspects are the short management period and the duration of Islamic Spirituality activities which are the same as other extracurricular activities. In the early stages of Islamic Spirituality mentoring, many of the Islamic Spirituality mentoring participants were XI students. Classes whose mental abilities and intelligence are low, are not mentally ready to become administrators. While the aspects that strengthen it include the facilities provided by the school, the financing of Islamic Spiritual activities, and the school's support for Islamic Spiritual activities. Through the implementation of Islamic Spirituality extracurricular guidance, students are able to develop their spiritual intelligence through tangible traits: a sense of closeness to Allah, determination, tawadu, honesty and patience.